Biosynthesis of Metal Oxide Nanoparticles - Chan, Stephanie (ChemBioEng Reviews, 2016)
Bioresource-based green synthesis of nanoparticles has gained significant interest as an emerging technology to reduce the toxicity of nanoparticles commonly associated with conventional chemical synthesis approaches. Studies on green synthesis of metal nanoparticles have been carried out with various biological materials including from bacteria, fungi, and plant extracts. Plant extracts in particular have been extensively used for the synthesis of metal and metal oxide nanoparticles, and this is due to the presence of essential phytochemicals in plant extracts especially from the leaves. Leaf extract contains various types of phytochemicals such as terpenoids, flavonoids, ketones, aldehydes, amides, and carboxylic acids, which play a major role in formulating and enhancing the bioactivity of the nanoparticles. This article discusses flavonoids as an essential phytochemical for the formation of metal and metal oxide nanoparticles and enhancement of their bio-functionality and compatibility. In addition, bioprocess developments for the synthesis of metal as well as metal oxide nanoparticles from various biological materials are discussed.